Public health concerns regarding sporadic Creutzfeldt–Jakob disease in China: a case series. Issue 8 (August 2019) - Zhou, Ru-Yi; Zhou, Yinzhu; Zhang, Heng; Hu, Qingqing; Zhu, Jinjie; Zhao, Jin; Chen, Shuilian; Liu, Ruchun; Hu, Weihong; Zhang, Xixing; Xuan, Xianfa; Liao, Yuxue; et al.
In this study, we report three cases of sporadic Creutzfeldt–Jakob disease in China, two confirmed cases and one probable case. The aim of this study was to enrich the data regarding clinical and epidemiological features of this disease and to provide reference for the diagnosis, control, and prevention of sporadic Creutzfeldt–Jakob disease.